Metzingera 'Duchowość a uczciwość intelektualna'. Komentarz - Łukasz Jędrzejczak (Avant, 2014)
The author comments on the essay "Spirituality and Intellectual Honesty" by Thomas Metzinger. He attempts to draw further conclusions from the Philosopher’s account.